PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PENGGUNA HANDPHONE SAMSUNG PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Hardjono Hardjono; Ika Wahyuni (Relawan Jurnal Indonesia, 2019)
This study aims to (1) to determine the effect of partially variabel product quality, price variables, and brand image on consumer satisfaction variable (2) to find out simultaneously the product quality variables, price variables, and brand image variables on consumer satisfaction variables (3) to find out between product quality variables, price variables, and brand image variables on cussumer satisfaction variables. The method used in this research is quantitative method. The result of research is multiple linear regression equationY = 4.715E - 16+ + + 0,270 + e. Partially the product quality has a significant positive effect with tcount of 2,869 equal to 1,99394,the price has a significant positive 3,089 equal to 1,99394, and the brand image has a significant effect with tcount of 2,744 equal to 1,99394. Simultaneously product quality, price, and brand image affect consumer satisfaction with value equal to 11,454, equal to 2,74. The dominant variable in this study is the value of 3,089.